The Effect of Tactile – Kinesthetic Stimulation on Bone Mineralization, Osteocalcin Levels and Body Height Among Stunting Children Aged 6-11 Months - Sutarmi, Sutarmi; Susanto, Hardhono; Mexitalia, Maria; Medise, Bernie (Universitas Pendidikan Indonesia, 2024)
Introduction: Stunting is growth faltering caused by as poor nutrition, recurrent infections, a lack of psychosocial stimulation. Growth faltering is associated to bone growth disorder. In order to prevent and overcome stunting not only nutrition but also an adequate stimulation is needed. Objective: This study looked at the effects of tactile–kinesthetic stimulation on bone mineralization, osteocalcin levels and body height among stunting children. Methods: Eighty (80) stunting children (mean of age 8 ± 1,71) were randomly assigned into two groups. Tactile–Kinesthetic Stimulation (TKS) was administrated by trained parents twice daily for three months in the intervention group. The control group was given a routine care of stunting program from public health center. The bone mineralization (osteocalcin serum) and length of body in both groups were measured at enrollment and after week twelve. Results: During three (3) months TKS period, the intervention group had a significant increment in length and osteocalcin serum compared to control group (p 0.005) at 3.17 cm and 11.5 ng/ml respectively. Moreover, this study also showed that providing TKS demonstrated a strong correlation in a positive direction to length. The TKS treatment could increase the body height of stunting children by 86.5%. There was a positive correlation among osteocalcin levels, intake of vitamin A, protein and calcium on improving length (p0.05). Conclusion: TKS was significantly effective in promoting bone mineralization particularly osteocalcin levels and length among stunting children. There was also a strong correlation that TKS could elevate the length of 0.865-times.